A Model of Strategic Thinking: Islamic and Iranian Perspective - Monavvarian, Abbas (International Journal of Business, Economics and Management, 2014)
Purpose - This research is trying to explore elements of strategic thinking from Islamic – Iranian point of views. Design/Methodology/Approach -The research method is qualitative. The main instruments of data and information collection are planned interview and library method. There was no sampling in this research. The researcher selected 17 elites (experts) familiar with the strategic management and strategic thinking. Findings - The study has found elements of strategic thinking are: Insight and foresight (Proactive), Analytical ability, Systems thinking, Creativity, Learning, Goal oriented Vision and Familiarity with modern science. Research limitations/implications -There are some limitations evident in this research. First, the researcher is from academic institute, so is not so familiar with Islamic literature. It means, if there is any deficiency in the literature is due to the low knowledge of the researcher. Second, although the sample size was sufficient, a larger sample may have provided better results.